An Analysis of Main Characters and Characterization in the Fatherhood Movie - Toruan, Betari Ardhana Lumban; Ramdhani, Muhammad Iqbal (Universitas Nahdlatul Ulama Blitar, 2023)
This study problems are to identify the factors contributing to becoming a single parent and how his parenting style is found in the Fatherhood movie. This study aims to find out the characterization in the movie by analyzing dialogue and scenes. to reveal the factors that occur until the role of a single parent and find out how parenting is being a single parent. This study applies the descriptive-qualitative method and data collection taken from dialogue and scenes. The results of this study found that there were eight characterizations of Matthew Logelin and six characterizations of Maddy Logelin. Grouped them into six ways of characterization based on the theory. This study found that there were three factors that caused Matthew to become a single parent, and there were three parenting styles. This research is recommended for those who are interested in the world of movies, analyzing characterization, and examining parenting styles.